2022
DOI: 10.1097/brs.0000000000004414
|View full text |Cite
|
Sign up to set email alerts
|

The T4-L1-Hip Axis

Abstract: Study Design. This is a cross-sectional cohort. Objective. The aim was to describe sagittal plane alignment and balance in a multinational cohort of nondegenerated, asymptomatic adults. Summary of Background Data. Current sagittal alignment targets were developed using correlations between radiographic and quality-of-life measures in spinal deformity patients, rather than disease-free samples leading to relatively poor accounting for variance within a population. Materials and Methods. Sagittal balance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Analyses from asymptomatic volunteers, without spinal degeneration, in the Multiethnic Alignment Normative Study showed that segmental alignment varies with pelvic incidence, and there is substantial interindividual variation in segmental alignment. 12 As such, we believe it is unlikely that useful segmental values at a patient-or pelvic incidencespecific level can be defined.…”
Section: Defining Normal Segmental Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses from asymptomatic volunteers, without spinal degeneration, in the Multiethnic Alignment Normative Study showed that segmental alignment varies with pelvic incidence, and there is substantial interindividual variation in segmental alignment. 12 As such, we believe it is unlikely that useful segmental values at a patient-or pelvic incidencespecific level can be defined.…”
Section: Defining Normal Segmental Alignmentmentioning
confidence: 99%
“…Analyses of normal (nondegenerated and nondeformed spines) confirmed the associations between spinal shape and pelvic incidence, though there are global alignment measures that are fairly consistent across pelvic incidence values. 12 One such measure is C2-tilt (angle subtended by a plumb line through the femoral heads and a line from the centroid of C2 to the femoral heads), also known as the "odontoid-hip-axis" (OD-HA). In normal posture, the C2-tilt and OD-HA are often −3° to +1°.…”
Section: Evolving Understanding Of Alignmentmentioning
confidence: 99%
“…These concepts will continue to evolve because our understanding of normative alignment grows. 12 Finally, MIS techniques are most limited in their ability to restore the sagittal plane to the desired degree, at times leading to poor patient-reported outcomes. Than et al 13 conducted a retrospective review of 104 patients who had undergone cMIS or hybrid surgery for ASD and concluded that postoperative PI-LL mismatch and failure to correct sagittal vertical axis (SVA) were associated with least clinical improvement after surgery.…”
Section: Restore Alignmentmentioning
confidence: 99%
“…The pelvic angle of incidence plays an important role in lumbar lordosis. 3,4 Lumbar lordosis is a unique structural feature of the normal human spine. Phylogenetically, it is considered a structural adaptation to upright walking 5 and places the torso's center of mass over the hips, improving the ability to withstand gravity.…”
Section: Introductionmentioning
confidence: 99%